Bureaucratic Performance in the Distribution of Social Aid for the Family Hope Program (PKH) at the Social Services of Langkat District - Sirait, Alfrida Rosalina; Hartono, Budi; Lubis, Maksum Syahri (Formosa Journal of Social Sciences (FJSS), 2024)
This research aims to analyze the performance of the bureaucracy in distributing social assistance for the Family Hope Program (PKH) at the Langkat Regency Social Service. PKH social assistance is a program that aims to reduce poverty and improve community welfare by providing regular cash assistance to poor families. However, the effectiveness of this program is very dependent on the performance of the bureaucracy in organizing the distribution of this aid. Data analysis was carried out using a descriptive method to explain the performance of the bureaucracy in implementing the PKH program. The research results show that the bureaucratic performance in administering PKH social assistance in Langkat Regency has several weaknesses, including the slow process of distributing aid, a lack of coordination between related agencies, and irregularities in aid distribution. These factors hinder the effectiveness of the program and cause dissatisfaction among aid recipients. Based on these findings, it is recommended that the Langkat Regency Social Service improve coordination between related agencies, improve the aid distribution system, and increase supervision of the implementation of the PKH program. Necessary to strengthen the capacity of field officers through training and education related to social assistance management. This is expected to improve bureaucratic performance in implementing the PKH program so that the program's goal of reducing poverty can be achieved more optimally